Case Report: Multimodality Imaging as a Lifeline for Fatal Localization of Valsalva Sinus Fibroelastoma - Tadic, Snezana; Ilic, Aleksandra; Stefanovic, Maja; Stojsic-Milosavljevic, Anastazija; Popov, Tanja; Bjelobrk, Marija; Milovancev, Aleksandra; Maksimovic, Nebojsa; Drid, Patrik (Frontiers in Cardiovascular Medicine, 2021)
Background: Papillary fibroelastomas are rare benign heart tumors, and is most likely to involve the cardiac valves.. We will present an extremely rare localization of a large Valsalva sinus fibroelastoma, with occasional left coronary artery ostial obstruction presented as an acute coronary syndrome. The tumor was removed surgically and histologically confirmed as papillary fibroelastoma. This review points to the crucial importance of multidisciplinary team decision and multimodality imaging methods for diagnosing the fibroelastoma, determination of size, and localization, which avoided complications of fatal embolization during an invasive procedure. Case Summary: A healthy 55-year-old male with vigorous physical daily training and exercise was admitted to the acute coronary syndrome emergency department. Shortly after admission, expert transthoracic echocardiography was performed. Computed tomography of the chest observed a large irregular hypodense tumor-like lesion in the bulbar aorta that was occasionally prolapsing into the left main coronary artery ostium and which corresponded to fibroelastoma. A few hours after admission, an emergency cardiac surgery was performed with the excision of a Valsalva sinus tumor (size 2x2 cm) located between the right and left coronary cusp of the aortic valve. Conclusions: Focus cardiac ultrasound should be performed for any acute coronary syndrome because of the possible Valsalva sinus fibroelastoma etiology. Its localization next to the left main coronary artery ostium is rare, and dangerous . The timely diagnosis can be made by the multimodality imaging method, however, the final diagnosis will be made pathohistologically. Early cardiac surgery may be a necessitated recourse for these patients in order to prevent a fatal outcome.